2017
DOI: 10.1016/j.ijheh.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic PM2.5 exposure and risk of infant bronchiolitis and otitis media clinical encounters

Abstract: Chronic particulate matter less than 2.5μm in diameter (PM2.5) exposure can leave infants more susceptible to illness. Our objective is to estimate associations of the chronic PM2.5 exposure with infant bronchiolitis and otitis media (OM) clinical encounters. We obtained all first time bronchiolitis (n=18,029) and OM (n=40,042) clinical encounters among children less than 12 and 36 months of age, respectively, diagnosed from 2001–2009 and two controls per case matched on birthdate and gestational age from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…In British Columbia, Canada, infants living within 50 meters of a highway had a 6% higher risk of bronchiolitis diagnosis, and infants living within 150 m of a highway had a 14% higher risk of hospitalization for respiratory syncytial virus (RSV) bronchiolitis infection; however, the confidence intervals for both estimates included the null 15, 16 . Another proximity study observed a statistically significant increased risk of bronchiolitis clinical encounters for infants living in areas of dense traffic, but found chronic PM 2.5 exposure alone was not meaningfully associated with infant bronchiolitis 17 . A meta-analysis of 10 European birth cohorts found elevated and statistically significant associations between NO 2 and PM 10 with pneumonia in early childhood, but not PM 2.5 18 .…”
Section: Introductionmentioning
confidence: 96%
“…In British Columbia, Canada, infants living within 50 meters of a highway had a 6% higher risk of bronchiolitis diagnosis, and infants living within 150 m of a highway had a 14% higher risk of hospitalization for respiratory syncytial virus (RSV) bronchiolitis infection; however, the confidence intervals for both estimates included the null 15, 16 . Another proximity study observed a statistically significant increased risk of bronchiolitis clinical encounters for infants living in areas of dense traffic, but found chronic PM 2.5 exposure alone was not meaningfully associated with infant bronchiolitis 17 . A meta-analysis of 10 European birth cohorts found elevated and statistically significant associations between NO 2 and PM 10 with pneumonia in early childhood, but not PM 2.5 18 .…”
Section: Introductionmentioning
confidence: 96%
“…PM 2.5 have been proven to be the triggers for a variety of illnesses, such as bronchitis, asthma, diabetes, chronic obstructive pulmonary disease (COPD), and cardiovascular disease [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The International Agency for Research on Cancer (IARC) has classified outdoor air pollution and air pollution-derived PM as carcinogenic to humans.…”
Section: Introductionmentioning
confidence: 99%
“…One case control study (Girguis et al, 2017) evaluated lifetime exposure of PM2.5 on risk of clinical encounter for bronchiolitis and found no association.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (including four case control studies and four case crossover studies Abdul Rahman et al, 2017 ; Girguis et al, 2017 ; Karr et al, 2004 , 2006 , 2007 , 2009a , 2009b ; Segala et al, 2008 ) were eligible for our review. The review flowchart is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation